Facilitators and barriers to smoking cessation: a qualitative study among health professionals in Germany - Frederike Bokemeyer; Paulina Kiefer; Lea Schmidt; Kathleen Gali (BMC Health Services Research)
Abstract Background Tobacco consumption remains a leading cause of global morbidity and mortality and is a significant preventable health concern. Despite the known benefits of smoking cessation, many smokers face difficulties in maintaining abstinence and preventing relapse. In Germany, approximately 30% of individuals aged 14 and older are smokers, which reflects low smoking cessation rates and limited use of evidence-based smoking cessation interventions. Purpose This qualitative study aimed to explore experts’ views on smoking cessation through interviews with health practitioners. Methods Fifteen semi-structured in-depth interviews were conducted with professionals from diverse fields, including medical doctors, psychologists, and addiction therapists, from July to November 2022. The data were analyzed using qualitative content analysis. A deductively developed categorization system was applied to identify sub-themes within categories and to systematically code the data. All data were thencategorized under two main categories: facilitators and barriers to smoking cessation. Results Key facilitators included the self-motivation of participants, the communication skills of the intervention leader, and the provision of knowledge about addiction mechanisms. Important barriers were smokers’ fears of quitting, external environmental pressures, and inadequate counseling structures. Conclusion The findings suggest that improving smoking cessation interventions in Germany require comprehensive strategies involving both structural adjustments in health care settings and enhanced training for tobacco treatment specialists.